MEASURING CUSTOMER PROFITABILITY WITH ACTIVITY-BASED COSTING AND BALANCED SCORECARD - CORDOȘ, Ildikó Réka; CORDOȘ, Vasile Daniel (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
In the last years many organizations realized that each customer is different; market orientation is essential to their success and the secret to improve profitability is to measure and manage customer profitability. Identifying and separating the most profitable customers from the less profitable ones; reducing the erosion of profit by customers; focusing on long-term customer profitability are only a few of those objectives that provides routes to a clear strategy for profitable growth. Although customer profitability analysis is considered to be a marketing topic it is considered as an important managerial accounting innovation in the same time and represents attractive research topic because of its novelty and exploding growth. Having in mind these aspects the remainder of this paper is structured as follows: first the background of managerial accounting is established by presenting the four evolution stages of managerial accounting. We would like to point out that the new challenge of managerial accounting is customer orientation and customer profitability analysis. Second, based on the existing literature in the field, we focus on the conceptual framework of customer profitability analysis. Third, we focus on the managerial accounting tools associated with customer profitability analysis. We would like to emphasize that combining customer profitability analysis with an activity-based costing system and balanced scorecard organizations can measure customer profitability accurately, gaining valuable information that enables companies to transform unprofitable relationships into profitable ones. Finally, conclusions are drawn in order to establish future research objectives.